Etoricoxib as a treatment of choice for patients with SLCO2A1 mutation exhibiting autosomal recessive primary hypertrophic osteoarthropathy: A case report - Albawa'neh, Areej; Al Mansoori, Mariam Ghareeb; Diab, Sehriban; Al Jasmi, Fatma; Akawi, Nadia (Frontiers in Genetics, 2022)
We report a 22-year-old Emirati male with autosomal recessive primary hypertrophic osteoarthropathy caused by a new homozygous nonsynonymous mutation in SLCO2A1 gene (NM_005630.3: c.289C>T, p.Arg97Cys) presenting with joint swelling, forehead furrowing, and significant clubbing in all fingers and toes. Currently, no standard treatments are approved for this disease, medical care is palliative and includes nonsteroidal anti-inflammatory drugs, corticosteroids, tamoxifen, retinoids, and risedronate. Colchicine may be helpful for the pain due to subperiosteal new bone formation. Our patient was treated with etoricoxib 60mg once daily and showed a significant clinical improvement at the six months mark that was reversed upon withdrawal of this medication. This case report highlights the importance of placing etoricoxib among first-line therapy recommendations for cases with confirmed primary hypertrophic osteoarthropathy diagnosis. To our knowledge this is the only case of primary hypertrophic osteoarthropathy from middle eastern population of Arabs ethnicity that has responded to non-steroidal anti-inflammatory drugs therapy.